Ethical values and norms in the communication systems of public institutions - Adamus-Matuszyńska, Anna; Polok, Grzegorz (Journal of Public Governance, 2019)
Objectives: This article aims to provide a theoretical analysis of communication in public institutions with regard to ethical values and norms. More specifically, the objective is to try to understand how ethics is anchored in communication systems in organizations acting on behalf and for the community.Research Design & Methods: The paradigm which the authors refer to is the social communication theory, theories of professional ethics and writings of management specialists who work in the field of organisational communication.Findings: While exploring the literature in the said fields, the authors draw analytical conclusions regarding values and norms which should (normative approach) characterise the system of internal and external communication in public institutions, undertaking an attempt to build a theoretical model at the same time.Implications / Recommendations: The analysis shows that the values and norms necessary for public institutions to operate properly are connected primarily with the need for all groups of stakeholders focused around this process to co-operate.Contribution / Value Added: The authors try to organise the values and norms typical for communication systems in public institutions into a model.